Analisis terhadap Kewenangan Jaksa Mengajukan Kasasi atas Putusan Bebas (Vrijspraak) dalam Perkara Pidana - Mariska Regina Martha; Syamsuri (Jurisprudensi: Jurnal Ilmu Hukum, 2025)
Judicial power is a key pillar of the rule of law in Indonesia. In criminal proceedings, acquittal (vrijspraak) decisions raise debate because Article 244 of the Criminal Procedure Code (KUHAP) normatively prohibits prosecutors from filing cassation against acquittals. However, Supreme Court jurisprudence and Constitutional Court Decision No. 114/PUU-X/2012 have opened limited space for such cassation. This study analyzes the prosecutor’s authority, its legal basis and limits, and its implications for legal certainty and justice, using authority theory within normative legal research (conceptual and legislative approaches) based on KUHAP, jurisprudence, and Constitutional Court decisions. The findings show that the prosecutor’s cassation authority gains legitimacy through these legal developments but is restricted to non-pure acquittals, namely where the acquittal results from misapplication of law, excess of judicial authority, or non-legal considerations. Therefore, cassation against acquittals functions as a judicial correction mechanism to safeguard law enforcement and substantive justice.